Backing material, raw material composition and preparation method thereof, ultrasonic probe, and ultrasonic diagnostic equipment

By introducing acrylic resin and amine-based curing agent into the backing material to form a multiphase interface, and adding tungsten powder, lead powder and alumina powder, the mixing difficulty and uneven performance of existing backing materials when improving acoustic impedance and acoustic attenuation are solved, and the high acoustic attenuation and thermal conductivity are improved, while simplifying the process and reducing environmental pollution.

CN115873378BActive Publication Date: 2025-03-04WUHAN UNITED IMAGING HEALTHCARE CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202211680333.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-26
Publication Date
2025-03-04
Estimated Expiration
2042-12-26

AI Technical Summary

Technical Problem

When the existing backing materials increase the filling amount of tungsten powder to enhance acoustic impedance and acoustic attenuation, they encounter problems of difficulty in mixing and uneven performance, and the process is complex and contaminated.

Method used

By introducing acrylic resin into the raw material composition of the backing material reacts with an amine-based curing agent, a multiphase interface is formed, acoustic wave refraction and reflection are improved, the effect of acoustic energy conversion into thermal energy is enhanced, and tungsten powder, lead powder and alumina powder are added to the system to improve thermal conductivity.

Benefits of technology

The backing material that achieves high acoustic attenuation performance improves thermal conductivity and acoustic impedance, simplifies the process, reduces production costs, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004018622720000071
    Figure BDA0004018622720000071
  • Figure BDA0004018622720000072
    Figure BDA0004018622720000072
  • Figure BDA0004018622720000191
    Figure BDA0004018622720000191
Patent Text Reader

Abstract

The present invention discloses a backing material, a raw material composition and a preparation method thereof, an ultrasonic probe, and an ultrasonic diagnostic device. The raw material composition of the backing material includes an epoxy resin, an acrylic resin, and an amine curing agent; wherein the average molecular weight of the epoxy resin is 350-400, and the epoxy equivalent is 175-200 g / eq; the average molecular weight of the acrylic resin is 70-200, and the viscosity is 20000-40000 CP. The backing material prepared by the raw material composition of the backing material provided by the present invention has the performance of high acoustic attenuation. Furthermore, optional components such as tungsten powder, lead powder, and alumina powder can be added to the system to further improve the thermal conductivity, and the acoustic impedance can be adjusted by changing the system density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a backing material, a raw material composition and a preparation method thereof, an ultrasonic probe and ultrasonic diagnostic equipment. Background Art

[0002] Ultrasonic diagnostic equipment is an "electric-to-acoustic" signal converter that converts electrical signals into ultrasonic waves, and can convert ultrasonic reverse signals received from the object being tested into electrical signals. It is widely used in the field of medical ultrasonic diagnosis.

[0003] The materials used in ultrasonic diagnostic equipment mainly include sound-generating piezoelectric materials, matching layer materials and sound-absorbing backing materials. Among them, piezoelectric materials use the piezoelectric effect to achieve the mutual conversion between electrical energy and sound energy; the matching layer can achieve a smooth transition of acoustic impedance between the piezoelectric element and the object to be measured, so that the sound energy generated by the piezoelectric element can be transmitted into the object to be measured through the matching layer, so that the sound energy generated by the piezoelectric element can enter the object to be measured to the greatest extent; as a component of ultrasonic diagnostic equipment, the backing can provide physical support for the piezoelectric element on the one hand; on the other hand, due to the high attenuation backing of the same thickness, it can absorb more sound waves, reduce the sound energy reflected to the piezoelectric element, and then improve the quality of the waveform, thereby obtaining a narrower sound pulse and improving the resolution; in addition, the backing uses the scattering characteristics of its own structure and the viscosity of the material to convert sound energy into heat energy, achieving a sound absorption effect, eliminating the interference signal emitted by the transducer to the rear, and improving sensitivity.

[0004] At present, the backing material is generally made of epoxy resin plus tungsten powder, silicone rubber plus tungsten powder, epoxy resin plus mercuric chloride and other solid-solid composite materials. In order to make a backing material with high acoustic impedance and high acoustic attenuation, it is necessary to try to increase the filling amount of heavy metals such as tungsten powder in epoxy resins to make a high-density material, but there are the following problems:

[0005] In order to increase the mass percentage of tungsten powder in the tungsten powder / epoxy system, simply add tungsten powder to the epoxy system. When the volume percentage of tungsten powder reaches 30%, the liquid epoxy system is already very viscous. Continuing to increase the content of tungsten powder will make it difficult to mix the system evenly. Therefore, the method of increasing the mass percentage of tungsten powder in the epoxy system to improve the acoustic impedance and acoustic attenuation of the backing material is not feasible. In addition, the performance of the material is not uniform, and the poor bonding force affects the bonding performance; as the proportion of tungsten powder in the epoxy system increases, the acoustic attenuation performance tends to decrease, and the acoustic attenuation performance of the material is poor and cannot meet practical requirements.

[0006] China Patent Publication No. CN1605863A, Publication Date April 13, 2005, Invention Name: "A Backing Material for Ultrasonic Non-destructive Testing Probe and Its Manufacturing Method", This application discloses a method of using a deposition method to make a backing material with high acoustic impedance and acoustic attenuation coefficient, The method is: dissolving soft thermoplastic resin particles in an organic solvent, adding tungsten powder and stirring, then evaporating the solvent, and finally making the backing material by hot pressing. The backing material made in this way can reach an acoustic impedance of 18.1×106Pa.s / m, and its acoustic attenuation coefficient at 5MHz is 105.1dB / cm. This process also has the following shortcomings: 1. The production process is relatively cumbersome, the time is relatively long, and it is not very suitable for industrial production; 2. Due to the use of volatile organic solvents, it is easy to cause pollution and unnecessary waste.

[0007] Chinese patent number CN104552718A, "A method for preparing a high attenuation backing material", discloses a method for preparing a high attenuation backing material by hot pressing, wherein tungsten powder is put into a mixing machine to mix evenly with polyurethane, polyvinyl chloride, and polyamide, and hot pressing is performed. The sound attenuation of the backing material prepared by this method can reach 50.9dB / cm / MHz. The shortcomings of this method are: 1. The manufacturing process is poorly stable, and it is difficult to achieve consistency in backing performance, which is not conducive to industrial production; 2. Due to the use of mechanical mixing, it is difficult to mix tungsten powder and resin evenly.

[0008] Chinese patent number CN 109907775A, "Backing component in ultrasonic probe", applicant: General Electric Company, this application discloses a method of using epoxy resin and tungsten powder, forming different density stacking layers by different material stacking densities, bonding the base layers with adhesives to form a backing, and increasing the number of backing interfaces and improving sound attenuation by changing the stacking density of the backing material. The shortcomings of this method are: poor manufacturing process stability, difficulty in achieving consistency in backing performance, and not conducive to industrial production. Summary of the invention

[0009] The technical problem to be solved by the present invention is to overcome the shortcomings of the backing material in the prior art, and provide a backing material, a raw material composition and a preparation method thereof, an ultrasonic probe, and an ultrasonic diagnostic device. The backing material prepared by the raw material composition of the backing material provided by the present invention has high acoustic attenuation performance. Furthermore, optional components such as tungsten powder, lead powder and alumina powder can be added to the system to further improve the thermal conductivity. By changing the system density, the acoustic impedance can be adjusted, and the preparation method of the backing material is simpler.

[0010] The present invention solves the above technical problems through the following technical solutions.

[0011] During the research process, the applicant creatively introduced acrylic resin into the conventional backing material composition. The acrylic resin reacted with the amine curing agent, the system phase separated, and a multiphase interface was formed. The number of interfaces of the backing material increased, which is conducive to improving the refraction and reflection of sound waves. The sound energy is continuously refracted and reflected in the multiphase interface, and the energy of the sound waves is reduced and converted into heat energy, which is eventually dissipated, thereby improving the sound attenuation of the backing system. In addition, the high damping and material viscosity of the acrylic resin are conducive to converting sound energy into heat energy, thereby achieving the purpose of sound absorption.

[0012] The present invention provides a raw material composition of a backing material, which comprises an epoxy resin, an acrylic resin and an amine curing agent;

[0013] The average molecular weight of the epoxy resin is 350-400, and the epoxy equivalent is 175-200; the average molecular weight of the acrylic resin is 70-200, and the viscosity is 20000-40000 CP.

[0014] In the present invention, the average molecular weight of the epoxy resin is preferably 370-380, for example, 375.86.

[0015] In the present invention, the epoxy equivalent of the epoxy resin is preferably 184 to 194 g / eq.

[0016] In the present invention, the epoxy resin may be a glycidyl ether epoxy resin, a modified glycidyl ether epoxy resin or a non-modified glycidyl ether epoxy resin.

[0017] Among them, the glycidyl ether epoxy resin is preferably one or more of E51 bisphenol A epoxy resin, aluminum oxide modified epoxy resin, semi-silicone modified bisphenol A epoxy resin, hyperbranched epoxy resin, bisphenol A epoxy hybrid resin, silicon-titanium hybrid epoxy resin and acrylic acid modified alkyd-epoxy ester hybrid resin, more preferably E51 bisphenol A epoxy resin, such as E51 glycidyl ether epoxy resin purchased from Baling Petrochemical, model CYD-128.

[0018] In the present invention, the average molecular weight of the acrylic resin is preferably 150-180.

[0019] In the present invention, the acrylic resin can be obtained by polymerizing one or more monomers selected from methyl acrylate, methyl methacrylate, ethyl methacrylate and propyl methacrylate, such as the acrylic resin purchased from Guangdong Keding Functional Materials Co., Ltd. with model number MR1616B.

[0020] In the present invention, the mass ratio of the epoxy resin to the acrylic resin may be (4-25):1, preferably (5-25):1, such as 5:1, 6.67:1, 10:1, 12.5:1 or 25:1.

[0021] In the present invention, the amine curing agent may be an amine curing agent containing a tertiary amine group, such as 593 type epoxy resin amine curing agent.

[0022] In the present invention, the mass ratio of the epoxy resin to the amine curing agent may be (3-5):1, for example, 4:1.

[0023] In the present invention, the raw material composition of the backing material may further include one or more of tungsten powder, lead powder and alumina powder.

[0024] The type of tungsten powder can be conventional in the art, preferably tungsten powder purchased from Beijing Zhongke Jinyan with model number DK-W-005.

[0025] The mass ratio of the epoxy resin to the tungsten powder may be (4-6):1, for example, 5:1. Tungsten powder, as a filler in the backing material, can further improve the acoustic attenuation performance of the backing material.

[0026] The type of the lead powder can be conventional in the art, preferably the lead powder purchased from Beijing Zhongke Jinyan with model number DK-Pb-01.

[0027] The mass ratio of the epoxy resin to the lead powder may be (8-12):1, for example, 10:1. The lead powder and tungsten powder have high density, which can increase the overall density of the backing material and further increase the acoustic impedance.

[0028] The type of aluminum oxide can be conventional in the art, preferably purchased from Aladdin, CAS No. 1344-28-1, model A102002-500g. Aluminum oxide is a powder material with high thermal conductivity and high sound velocity. Adding aluminum oxide to this system can improve the thermal conductivity and sound velocity of the backing material.

[0029] Wherein, the mass ratio of the epoxy resin to the aluminum oxide may be (18-22):1, for example, 20:1.

[0030] In the present invention, the raw material composition of the backing material may further include one or more of a thixotropic agent, a defoaming agent and a coupling agent.

[0031] The thixotropic agent may be fumed silica, preferably fumed silica purchased from Evonik Degussa with model number R202.

[0032] Wherein, the mass ratio of the epoxy resin to the thixotropic agent may be (150-180):1, preferably 166.7:1.

[0033] The defoaming agent may be polydimethylsiloxane, preferably a defoaming agent purchased from Dow Chemical with a model number of PMX-200.

[0034] Wherein, the mass ratio of the epoxy resin to the defoaming agent may be (90-110):1, preferably 100:1.

[0035] The coupling agent may be one or more of the silane coupling agents KH550 (γ-aminopropyltriethoxysilane), KH560 (γ-(2,3-epoxypropyloxy)propyltrimethoxysilane) and KH570 (γ-methacryloxypropyltrimethoxysilane).

[0036] Wherein, the mass ratio of the epoxy resin to the coupling agent may be (60-70):1, for example, 66.7:1.

[0037] Preferably, the raw material composition of the backing material includes epoxy resin, acrylic resin, amine curing agent, tungsten powder, lead powder, aluminum oxide powder, thixotropic agent, defoaming agent and coupling agent.

[0038] In some preferred embodiments of the present invention, the raw material composition of the backing material includes, by mass fraction, 100 g of epoxy resin, 4 to 25 g of acrylic resin, 25 g of amine curing agent, 20 g of tungsten powder, 10 g of lead powder, 5 g of aluminum oxide, 0.6 g of thixotropic agent, 1 g of defoaming agent and 1.5 g of coupling agent.

[0039] The invention provides a method for preparing a backing material, which comprises the following steps: mixing and reacting the raw material composition of the backing material to prepare the backing material.

[0040] In the present invention, preferably, the amounts of the components in the raw material composition of the backing material are as described above.

[0041] In the present invention, the mixing method is preferably a mechanical stirring method.

[0042] In the present invention, the reaction can be carried out at room temperature, which can be 15 to 25° C. as commonly understood in the art, such as 25° C.

[0043] In the present invention, the relative humidity of the reaction may be 40-60% RH, for example 50% RH.

[0044] In the present invention, the reaction time may be 12 to 48 hours, for example 24 hours.

[0045] In a preferred embodiment, the method for preparing the backing material comprises the following steps:

[0046] At 25°C, add 100g of E51 epoxy resin into a 250ml flask, add 0.1-10g of acrylic resin, 20g of tungsten powder, 10g of lead powder, and 5g of alumina into the flask and stir for 10min, add 0.6g of fumed silica into the flask and stir for 10min, then add 1g of polydimethylsiloxane and 1.5g of KH560 into the flask and stir for 10min, finally add 25g of 593 epoxy resin amine curing agent into the reaction system and stir for 10min to obtain a uniformly mixed epoxy resin, then cast the prepared epoxy resin into a molding mold, put it into a constant temperature and humidity chamber at 25°C and 50%RH for curing for 24h to obtain a backing material.

[0047] The invention also provides a backing material, which is prepared by the method.

[0048] In the present invention, the number average molecular weight of the backing material may be 340-380, preferably 360-367, for example 360, 361, 362, 364, 365 or 367.

[0049] In the present invention, the number average molecular weight refers to the average molecular weight of the backing material.

[0050] In the present invention, the number average molecular weight of the backing material is generally smaller than the average molecular weight of the epoxy resin.

[0051] In the present invention, the molecular weight distribution of the backing material may be 340-400, preferably 350-385, for example 350-380, 350-382, 355-380, 355-382, 356-380, 360-380 or 360-385.

[0052] In the present invention, molecular weight distribution refers to the molecular weight distribution range.

[0053] In the present invention, the density of the backing material can be 1.0 to 6.0 g / cm 3 , preferably 1.16 to 5.63 g / cm 3 , for example 1.16 g / cm 3 , 1.78g / cm 3 , 1.8g / cm 3 , 1.96g / cm 3 4.46g / cm 3 , 5.6g / cm 3 or 5.63g / cm 3 .

[0054] In the present invention, the viscosity of the backing material may be 4000-30000CP, preferably 4800-25500CP, such as 4800CP, 5000CP, 5200CP, 5300CP, 5500CP, 5700CP, 6000CP, 23500CP, 25000CP or 25500CP. The viscosity is measured using GB / T22314-2008- "Method for Determination of Viscosity of Plastic Epoxy Resins", and the viscosity η is defined by the following formula: η=τ / γ,

[0055] Where:

[0056] η——Viscosity, in Pascal seconds (Pa*s)

[0057] τ——shear force, in Pascal (Pa)

[0058] γ——shear speed, in s per second -1 ).

[0059] In the present invention, the viscosity of the backing material is generally lower than the viscosity of the acrylic resin.

[0060] In the present invention, the sound velocity of the backing material may be 1600 to 2500 m / s, preferably 1650 to 2465 m / s, such as 1650 m / s, 1675 m / s, 1690 m / s, 2189 m / s, 2200 m / s, 2310 m / s, 2315 m / s, 2323 m / s, 2415 m / s or 2465 m / s. The sound velocity is measured by the water immersion insertion method, and the sound velocity coefficient can be expressed as:

[0061]

[0062] Among them, △l is the thickness difference of the inserted sample, △t is the sound propagation time difference caused by inserting samples of different thicknesses, and c w is the speed of sound in water.

[0063] In the present invention, the acoustic impedance of the backing material may be 2.5 to 10 Mray, preferably 2.68 to 9.43 Mray, such as 2.68 Mray, 2.69 Mray, 2.7 Mray, 2.8 Mray, 2.86 Mray, 3.96 Mray, 4.13 Mray, 4.29 Mray, 7.54 Mray, 9.24 Mray or 9.43 Mray. The formula for acoustic impedance can be expressed as:

[0064] Z=ρ*c

[0065] Where ρ is the density of the test sample and c is the speed of sound in the test sample.

[0066] In the present invention, the acoustic attenuation of the backing material at a frequency of 2.25 MHz can be 70 to 90 dB / cm, preferably 73.51 to 89.05 dB / cm, such as 73.51 dB / cm, 80 dB / cm, 80.53 dB / cm, 81.30 dB / cm, 81.84 dB / cm, 82.03 dB / cm, 82.04 dB / cm, 83.07 dB / cm, 88.54 dB / cm, 88.74 dB / cm or 89.05 dB / cm. The acoustic attenuation is measured by the water immersion insertion method, and the acoustic attenuation coefficient can be expressed as:

[0067]

[0068] Where, l1 and l2 are the thickness of the test sample, α w is the acoustic attenuation coefficient in water, A1 and A2 are the pulse signal amplitudes received when testing samples with thicknesses of l1 and l2 respectively.

[0069] In the present invention, the thermal conductivity of the backing material may be 0.2 to 1.6 W / m·K, preferably 0.22 to 1.54 W / m·K, such as 0.22 W / m·K, 0.221 W / m·K, 0.223 W / m·K, 0.27 W / m·K, 0.33 W / m·K, 0.42 W / m·K, 1.532 W / m·K, 1.538 W / m·K or 1.54 W / m·K. The thermal conductivity is measured using the international standard ISO 22007-2 "Plastics. Determination of thermal conductivity and thermal diffusivity".

[0070] The present invention also provides an ultrasonic probe, which comprises the above-mentioned backing material.

[0071] The present invention also provides an ultrasonic diagnostic device, which comprises the ultrasonic probe.

[0072] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0073] The reagents and raw materials used in the present invention are commercially available.

[0074] The positive and progressive effects of the present invention are:

[0075] 1. The present invention adds acrylic resin to the raw materials, and after the chemical characteristics and physicochemical properties of each component are combined, the obtained backing material has the performance of high sound attenuation. Furthermore, optional components such as tungsten powder, lead powder and aluminum oxide powder can be added to the system to further improve the thermal conductivity. By changing the system density and adjusting the acoustic impedance, it can be applied to ultrasonic diagnostic equipment, ensuring the ultrasonic diagnostic equipment's requirements for the acoustic performance, bonding performance, cutting performance and heat dissipation performance of the backing material.

[0076] Among them, the high thermal conductivity of the backing material is conducive to improving the thermal conductivity of the backing material and reducing the problem of excessive temperature when the transducer is working; the good high attenuation performance eliminates the interference signal emitted by the transducer to the rear, reduces the sound energy reflected on the piezoelectric element, and no back noise is generated, thereby improving the quality of the waveform and the resolution of the probe; the low acoustic impedance ensures the sensitivity of the probe.

[0077] 2. The backing material of the present invention has a simple source of materials, low price, simple and quick manufacturing process, is conducive to industrial production, and will not cause waste and environmental pollution, effectively ensuring the production cost of ultrasonic diagnostic equipment. DETAILED DESCRIPTION

[0078] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0079] In the following examples and comparative examples, the sources of the raw materials are as follows:

[0080] Epoxy resin: E51 glycidyl ether epoxy resin purchased from Baling Petrochemical, model CYD-128; its average molecular weight is 375.86, and the epoxy equivalent is 184-194 g / eq.

[0081] Acrylic resin: purchased from Guangdong Keding Functional Materials Co., Ltd., model MR1616B8; its average molecular weight is 150-180, and its viscosity is 20000-40000 CP.

[0082] Terpene resin: purchased from Guangdong Kemao Forestry and Chemical Industry Co., Ltd., model KT10.

[0083] Butadiene rubber: purchased from Shenzhen Masini Elastomer Co., Ltd., model number is LBR-10K.

[0084] Amine curing agent: 593 type epoxy resin amine curing agent.

[0085] Tungsten powder: purchased from Beijing Zhongke Jinyan, model number is DK-W-005.

[0086] Lead powder: purchased from Beijing Zhongke Jinyan, model number is DK-Pb-01.

[0087] Alumina: purchased from Aladdin, CAS No. 1344-28-1, model A102002-500g.

[0088] Fumed silica: purchased from Evonik Degussa, model number R202.

[0089] Polydimethylsiloxane: purchased from Dow Chemical, model number is PMX-200.

[0090] Comparative Example 1

[0091] 100g E51 epoxy resin was added to a 250ml flask, 0.6g fumed silica was added to the flask and stirred for 10min, 1g polydimethylsiloxane and 1.5g KH560 were added to the flask and stirred for 10min, and finally 25g 593 epoxy resin amine curing agent was added to the reaction system and stirred for 10min to obtain a uniformly mixed epoxy resin, and then the prepared epoxy resin was poured into a molding mold and placed in a constant temperature and humidity chamber at 25°C and 50%RH for curing for 24h to obtain a sound backing material. The density of the epoxy resin cured product is 1.15g / cm 3 , the sound velocity is 2729m / s, the acoustic impedance is 3.14MRayl, the acoustic attenuation at a frequency of 2.25MHz is 13.84dB / cm, and the thermal conductivity is 0.21W / m*k.

[0092] Comparative Example 2

[0093] Add 100g E51 epoxy resin into a 250ml flask, add 20g tungsten powder into the flask and stir for 10min, add 0.6g fumed silica into the flask and stir for 10min, then add 1g polydimethylsiloxane and 1.5g KH560 into the flask and stir for 10min, finally add 25g 593 epoxy resin amine curing agent into the reaction system and stir for 10min to obtain a uniformly mixed epoxy resin, then cast the prepared epoxy resin into a molding mold, put it into a constant temperature and humidity chamber at 25℃ and 50%RH and cure for 24h to obtain a sound backing material. The density of the epoxy resin cured product is 4.45g / cm 3 , the sound velocity is 1719m / s, the acoustic impedance is 7.65MRayl, the acoustic attenuation at a frequency of 2.25MHz is 18.2dB / cm, and the thermal conductivity is 0.32W / m*k.

[0094] By comparing Comparative Example 2 with Comparative Example 1, it can be seen that after tungsten powder is added to the system of Comparative Example 1, the density of the system increases, which may be due to the large density of tungsten powder; the sound velocity of the system decreases, and the sound attenuation increases from 13.84dB to 18.2dB, which may be due to the presence of multiple epoxy resin-tungsten powder interfaces in the system, and the sound waves are refracted or reflected between the epoxy resin-tungsten powder interfaces, and the sound energy is reduced, resulting in a decrease in the sound velocity of the system and an increase in the sound attenuation; acoustic impedance = density * sound velocity. Due to the large increase in density, the acoustic impedance of the system increases; since the thermal conductivity of tungsten powder is greater than that of epoxy resin, the thermal conductivity of the system increases slightly.

[0095] Comparative Example 3

[0096] Add 100g E51 epoxy resin into a 250ml flask, add 20g tungsten powder and 10g lead powder into the flask and stir for 10min, add 0.6g fumed silica into the flask and stir for 10min, then add 1g polydimethylsiloxane and 1.5g KH560 into the flask and stir for 10min, finally add 25g 593 epoxy resin amine curing agent into the reaction system and stir for 10min to obtain a uniformly mixed epoxy resin, then cast the prepared epoxy resin into a molding mold, put it into a constant temperature and humidity chamber at 25℃ and 50%RH and cure for 24h to obtain a sound backing material. The density of the epoxy resin cured product is 5.5g / cm 3 , the sound velocity is 1685m / s, the acoustic impedance is 9.27MRayl, the acoustic attenuation at a frequency of 2.25MHz is 19dB / cm, and the thermal conductivity is 0.35W / m*k.

[0097] By comparing Comparative Example 3 with Comparative Example 2, it can be seen that after adding lead powder to the system of Comparative Example 2, the system density is further increased, the system sound velocity is further reduced, and the sound attenuation is slightly increased. This may be due to the fact that the sound waves produce more refraction or reflection at the epoxy resin-tungsten powder-lead powder interface; due to the greater increase in density, the system acoustic impedance increases; since the thermal conductivity of tungsten powder and lead powder is greater than that of epoxy resin, the thermal conductivity of the system is further increased.

[0098] Comparative Example 4

[0099] 100g E51 epoxy resin was added to a 250ml flask, 20g tungsten powder and 5g alumina were added to the flask and stirred for 10min, 0.6g fumed silica was added to the flask and stirred for 10min, 1g polydimethylsiloxane and 1.5g KH560 were added to the flask and stirred for 10min, and finally 25g 593 epoxy resin amine curing agent was added to the reaction system and stirred for 10min to obtain a uniformly mixed epoxy resin, and then the prepared epoxy resin was poured into a molding mold and placed in a constant temperature and humidity chamber at 25°C and 50%RH for curing for 24h to obtain a sound backing material. The density of the epoxy resin cured product is 4.67g / cm 3 , the sound velocity is 1710m / s, the acoustic impedance is 7.99MRayl, the acoustic attenuation at a frequency of 2.25MHz is 18.3dB / cm, and the thermal conductivity is 1.527W / m*k.

[0100] By comparing Comparative Example 4 with Comparative Example 2, it can be seen that after adding alumina to the system of Comparative Example 2, the system density, sound velocity, acoustic impedance and acoustic attenuation have no obvious changes; the thermal conductivity of the system is significantly increased, which may be due to the addition of metal particle alumina. Alumina has a large thermal conductivity (10W / m*k) and good thermal conductivity, which is beneficial to heat dissipation when the probe is working.

[0101] Comparative Example 5

[0102] Add 100g E51 epoxy resin to a 250ml flask, add 10g terpene resin to the flask and stir for 10min, add 0.6g fumed silica to the flask and stir for 10min, then add 1g polydimethylsiloxane and 1.5g KH560 to the flask and stir for 10min, finally add 25g 593 epoxy resin amine curing agent to the reaction system and stir for 10min to obtain a uniformly mixed epoxy resin, then pour the prepared epoxy resin into a molding mold, put it into a constant temperature and humidity chamber at 25℃ and 50%RH for curing for 24h to obtain a sound backing material. The density of the epoxy resin cured product is 1.15g / cm 3 , the sound velocity is 2200m / s, the acoustic impedance is 2.53MRayl, the acoustic attenuation at a frequency of 2.25MHz is 15.2dB / cm, and the thermal conductivity is 0.23W / m*k.

[0103] By comparing Comparative Example 5 with Comparative Example 1, it can be seen that after adding terpene resin to the system of Comparative Example 1, the density of the system does not change substantially, which may be due to the fact that the densities of terpene resin and E51 epoxy resin are comparable; the sound velocity of the system decreases and the sound attenuation increases, which may be due to the fact that terpene resin can phase separate from epoxy resin, and there are multiple epoxy resin-terpene resin interfaces in the system, and sound waves also refract or reflect between the interfaces, reducing the sound energy, thereby resulting in a decrease in the sound velocity and an increase in the sound attenuation, but the increase in the sound attenuation is small; the acoustic impedance of the system decreases as the sound velocity decreases; and the thermal conductivity of the system increases less.

[0104] Comparative Example 6

[0105] Add 100g E51 epoxy resin to a 250ml flask, add 10g cis-1,4-butadiene rubber to the flask and stir for 10min, add 0.6g fumed silica to the flask and stir for 10min, then add 1g polydimethylsiloxane and 1.5g KH560 to the flask and stir for 10min, finally add 25g 593 epoxy resin amine curing agent to the reaction system and stir for 10min to obtain a uniformly mixed epoxy resin, then pour the prepared epoxy resin into a molding mold, put it into a constant temperature and humidity chamber at 25°C and 50%RH for curing for 24h to obtain a sound backing material. The density of the epoxy resin cured product is 1.19g / cm 3 , the sound velocity is 2150m / s, the acoustic impedance is 2.56MRayl, the acoustic attenuation at a frequency of 2.25MHz is 25.3dB / cm, and the thermal conductivity is 0.227W / m*k.

[0106] By comparing Comparative Example 6 with Comparative Example 1, it can be seen that after adding butadiene rubber to the system of Comparative Example 1, the density of the system increases slightly, which may be due to the large density of butadiene rubber; the sound velocity of the system decreases and the sound attenuation increases, which may be due to the fact that butadiene rubber can phase separate from the epoxy resin, and there are multiple epoxy resin-butadiene rubber interfaces in the system. Sound waves also refract or reflect between the interfaces, and the sound energy decreases, thereby resulting in a decrease in the sound velocity and an increase in the sound attenuation; the acoustic impedance of the system decreases as the sound velocity decreases; and the thermal conductivity of the system increases slightly.

[0107] Example 1

[0108] Add 100g E51 epoxy resin to a 250ml flask, add 10g acrylic resin to the flask and stir for 10min, add 0.6g fumed silica to the flask and stir for 10min, then add 1g polydimethylsiloxane and 1.5g KH560 to the flask and stir for 10min, finally add 25g 593 epoxy resin amine curing agent to the reaction system and stir for 10min to obtain a uniformly mixed epoxy resin, then pour the prepared epoxy resin into a molding mold, put it into a constant temperature and humidity chamber at 25℃ and 50%RH and cure it for 24h to obtain a sound backing material. The density of the epoxy resin cured product is 1.16g / cm 3 , the sound velocity is 2315m / s, the acoustic impedance is 2.69MRayl, the acoustic attenuation at a frequency of 2.25MHz is 81.84dB / cm, and the thermal conductivity is 0.22W / m*k.

[0109] By comparing Example 1 with Comparative Example 1, it can be seen that after adding acrylic resin to the system of Comparative Example 1, the sound attenuation increases from 13.84 dB to 81.84 dB. This may be due to the reaction of acrylic resin with amine curing agent. After the reaction, the system separates with epoxy resin, which increases the number of interfaces of the backing material, which is beneficial to improving the refraction and reflection of sound waves. Sound energy is continuously refracted and reflected in the multiphase interface, and the energy of sound waves is reduced and converted into heat energy, which is finally dissipated, thereby increasing the sound attenuation of the system, and the sound velocity of the system is reduced and the acoustic impedance is reduced.

[0110] By comparing Example 1 with Comparative Examples 1-6, it can be seen that by adding acrylic resin to the system of Comparative Example 1, the sound attenuation is greatly improved; it is greater than the sound attenuation of adding tungsten powder, lead powder, aluminum oxide, terpene resin or butadiene rubber. The reason may be that by adding acrylic resin, there are more phase interfaces in the system, and the sound energy is continuously refracted and reflected in the multi-phase interface, and the energy of the sound wave is reduced and converted into heat energy, and finally dissipated, thereby improving the sound attenuation of the system; in addition, the high damping and material viscosity of acrylic resin are conducive to converting sound energy into heat energy.

[0111] Example 2

[0112] Add 100g E51 epoxy resin into a 250ml flask, add 20g tungsten powder and 10g acrylic resin into the flask and stir for 10min, add 0.6g fumed silica into the flask and stir for 10min, then add 1g polydimethylsiloxane and 1.5g KH560 into the flask and stir for 10min, finally add 25g 593 epoxy resin amine curing agent into the reaction system and stir for 10min to obtain a uniformly mixed epoxy resin, then cast the prepared epoxy resin into a molding mold, put it into a constant temperature and humidity chamber at 25℃ and 50%RH and cure for 24h to obtain a sound backing material. The density of the epoxy resin cured product is 4.46g / cm 3 , the sound velocity is 1690m / s, the acoustic impedance is 7.54MRayl, the acoustic attenuation at a frequency of 2.25MHz is 88.54dB / cm, and the thermal conductivity is 0.33W / m*k.

[0113] By comparing Example 2 with Comparative Example 1, it can be seen that after adding tungsten powder and acrylic resin to the system of Comparative Example 1, the acoustic attenuation increases from 13.84dB to 88.54dB. This may be because after adding tungsten powder and acrylic resin, the system phase interface is superimposed, so the acoustic attenuation increases and the sound velocity decreases. The acoustic attenuation is mainly caused by the formation of a multiphase interface between the acrylic resin and the system and the high damping and material viscosity of the acrylic resin. Due to the high density of tungsten powder, the density of the system increases; due to the large increase in density, the acoustic impedance of the system increases; because the thermal conductivity of tungsten powder is greater than that of epoxy resin and acrylic resin, the thermal conductivity of the system increases slightly.

[0114] From the comparison between Example 2 and Comparative Example 2, it can be seen that when acrylic resin is added to the system of Comparative Example 2, the sound attenuation is greatly increased due to the increase in the number of interfaces of the backing material.

[0115] Example 3

[0116] 100g E51 epoxy resin was added to a 250ml flask, 20g tungsten powder, 10g acrylic resin, and 10g lead powder were added to the flask and stirred for 10min, 0.6g fumed silica was added to the flask and stirred for 10min, 1g polydimethylsiloxane and 1.5g KH560 were added to the flask and stirred for 10min, and finally 25g 593 epoxy resin amine curing agent was added to the reaction system and stirred for 10min to obtain a uniformly mixed epoxy resin, and then the prepared epoxy resin was poured into a molding mold and placed in a constant temperature and humidity chamber at 25°C and 50%RH for curing for 24h to obtain a sound backing material. The density of the epoxy resin cured product is 5.6g / cm 3 , the sound velocity is 1650m / s, the acoustic impedance is 9.24MRayl, the acoustic attenuation at a frequency of 2.25MHz is 89.05dB / cm, and the thermal conductivity is 0.42W / m*k.

[0117] By comparing Example 3 with Example 2, it can be seen that after adding lead powder to the system of Example 2 at the same time, the density of the lead powder is large, resulting in a large density of the system. Due to the increase in the number of interfaces, the number of refractions or reflections increases, the sound velocity is slightly reduced, and the sound attenuation increases; due to the greater increase in density, the acoustic impedance of the system increases; since the thermal conductivity of tungsten powder and lead powder is greater than that of epoxy resin, the thermal conductivity of the system is further increased;

[0118] From the comparison between Example 3 and Comparative Example 3, it can be seen that when acrylic resin is added to the system of Comparative Example 3, the sound attenuation is greatly increased due to the increase in the number of interfaces of the backing material.

[0119] Example 4

[0120] 100g E51 epoxy resin was added to a 250ml flask, 20g tungsten powder, 10g acrylic resin, 10g lead powder, and 5g alumina were added to the flask and stirred for 10min, 0.6g fumed silica was added to the flask and stirred for 10min, 1g polydimethylsiloxane and 1.5g KH560 were added to the flask and stirred for 10min, and finally 25g 593 epoxy resin amine curing agent was added to the reaction system and stirred for 10min to obtain a uniformly mixed epoxy resin, and then the prepared epoxy resin was poured into a molding mold and placed in a constant temperature and humidity chamber at 25°C and 50%RH for curing for 24h to obtain a sound backing material. The density of the epoxy resin cured product is 5.63g / cm 3 , the sound velocity is 1675m / s, the acoustic impedance is 9.43MRayl, the acoustic attenuation at a frequency of 2.25MHz is 88.74dB / cm, and the thermal conductivity is 1.532W / m*k.

[0121] By comparing Example 4 with Example 3, it can be seen that after adding alumina to the system of Example 3, the density, sound velocity, acoustic impedance, and acoustic attenuation change slightly, but the thermal conductivity is greatly improved. This may be due to the large thermal conductivity of alumina (10W / m*k), which leads to a significant increase in the thermal conductivity of the system, which is beneficial to heat dissipation when the probe is working.

[0122] From the comparison between Example 4 and Comparative Example 4, it can be seen that when acrylic resin is added to the system of Comparative Example 4, the sound attenuation is greatly increased due to the increase in the number of interfaces of the backing material.

[0123] Example 5

[0124] Add 100g E51 epoxy resin into a 250ml flask, add 10g acrylic resin and 10g lead powder into the flask and stir for 10min, add 0.6g fumed silica into the flask and stir for 10min, then add 1g polydimethylsiloxane and 1.5g KH560 into the flask and stir for 10min, finally add 25g 593 epoxy resin amine curing agent into the reaction system and stir for 10min to obtain a uniformly mixed epoxy resin, then cast the prepared epoxy resin into a molding mold, put it into a constant temperature and humidity chamber at 25℃ and 50%RH and cure for 24h to obtain a sound backing material. The density of the epoxy resin cured product is 1.8g / cm 3 , the sound velocity is 2200m / s, the acoustic impedance is 3.96MRayl, the acoustic attenuation at a frequency of 2.25MHz is 80.53dB / cm, and the thermal conductivity is 0.27W / m*k.

[0125] By comparing Example 5 with Example 1, it can be seen that after adding lead powder to the system of Example 1, the density of the system increases, the sound velocity decreases slightly, the acoustic impedance increases, the sound attenuation changes slightly, and the thermal conductivity increases slightly.

[0126] By comparing Examples 1 and 5 with Comparative Examples 2 and 3, it can be seen that by adding the same amount of lead powder to the epoxy resin and acrylic resin system and to the epoxy resin and tungsten powder system, the former can significantly improve the sound attenuation without affecting the thermal conductivity.

[0127] Example 6

[0128] Add 100g E51 epoxy resin into a 250ml flask, add 10g acrylic resin and 5g alumina into the flask and stir for 10min, add 0.6g fumed silica into the flask and stir for 10min, then add 1g polydimethylsiloxane and 1.5g KH560 into the flask and stir for 10min, finally add 25g 593 epoxy resin amine curing agent into the reaction system and stir for 10min to obtain a uniformly mixed epoxy resin, then cast the prepared epoxy resin into a molding mold, put it into a constant temperature and humidity chamber at 25℃ and 50%RH and cure for 24h to obtain a sound backing material. The density of the epoxy resin cured product is 1.78g / cm 3 , the sound velocity is 2323m / s, the acoustic impedance is 4.13MRayl, the acoustic attenuation at a frequency of 2.25MHz is 82.03dB / cm, and the thermal conductivity is 1.538W / m*k.

[0129] By comparing Example 6 with Example 1, it can be seen that after adding alumina to the system of Example 1, the density and sound velocity of the system are increased, the acoustic impedance increases accordingly, the acoustic attenuation changes slightly, but the thermal conductivity is greatly improved. This may be due to the large thermal conductivity of alumina (10W / m*k), which leads to a significant increase in the thermal conductivity of the system, which is beneficial to heat dissipation when the probe is working.

[0130] From the comparison between Examples 1 and 6 and Comparative Examples 2 and 4, it can be seen that by adding the same amount of aluminum oxide to the system of epoxy resin and acrylic resin and to the system of epoxy resin and tungsten powder, the former can also significantly improve the sound attenuation without affecting the thermal conductivity.

[0131] Example 7

[0132] Add 100g E51 epoxy resin into a 250ml flask, add 10g acrylic resin, 10g lead powder, and 5g alumina into the flask and stir for 10min, add 0.6g fumed silica into the flask and stir for 10min, then add 1g polydimethylsiloxane and 1.5g KH560 into the flask and stir for 10min, finally add 25g 593 epoxy resin amine curing agent into the reaction system and stir for 10min to obtain a uniformly mixed epoxy resin, then cast the prepared epoxy resin into a molding mold, put it into a constant temperature and humidity chamber at 25℃ and 50%RH and cure for 24h to obtain a sound backing material. The density of the epoxy resin cured product is 1.96g / cm 3 , the sound velocity is 2189m / s, the acoustic impedance is 4.29MRayl, the acoustic attenuation at a frequency of 2.25MHz is 83.07dB / cm, and the thermal conductivity is 1.54W / m*k.

[0133] By comparing Example 7 with Example 1, it can be seen that after adding lead powder and alumina to the system of Example 1, the density of the system increases slightly, and the average acoustic impedance increases accordingly. Due to the increase in the number of interfaces of the backing material, the sound velocity decreases and the sound attenuation increases; the thermal conductivity is greatly improved, which may be due to the large thermal conductivity of alumina (10W / m*k), which leads to a significant increase in the thermal conductivity of the system, which is beneficial to heat dissipation when the probe is working.

[0134] Example 8

[0135] Add 100g E51 epoxy resin to a 250ml flask, add 4g acrylic resin to the flask and stir for 10min, add 0.6g fumed silica to the flask and stir for 10min, then add 1g polydimethylsiloxane and 1.5g KH560 to the flask and stir for 10min, finally add 25g 593 epoxy resin amine curing agent to the reaction system and stir for 10min to obtain a uniformly mixed epoxy resin, then pour the prepared epoxy resin into a molding mold, put it into a constant temperature and humidity chamber at 25℃ and 50%RH for curing for 24h to obtain a sound backing material. The density of the epoxy resin cured product is 1.15g / cm 3 , the sound velocity is 2300m / s, the acoustic impedance is 2.65MRayl, the acoustic attenuation at a frequency of 2.25MHz is 30.43dB / cm, and the thermal conductivity is 0.215W / m*k.

[0136] Example 9

[0137] Add 100g E51 epoxy resin to a 250ml flask, add 8g acrylic resin to the flask and stir for 10min, add 0.6g fumed silica to the flask and stir for 10min, then add 1g polydimethylsiloxane and 1.5g KH560 to the flask and stir for 10min, finally add 25g 593 epoxy resin amine curing agent to the reaction system and stir for 10min to obtain a uniformly mixed epoxy resin, then pour the prepared epoxy resin into a molding mold, put it into a constant temperature and humidity chamber at 25℃ and 50%RH for curing for 24h to obtain a sound backing material. The density of the epoxy resin cured product is 1.16g / cm 3 , the sound velocity is 2310m / s, the acoustic impedance is 2.68MRayl, the acoustic attenuation at a frequency of 2.25MHz is 73.51dB / cm, and the thermal conductivity is 0.221W / m*k.

[0138] Example 10

[0139] Add 100g E51 epoxy resin to a 250ml flask, add 15g acrylic resin to the flask and stir for 10min, add 0.6g fumed silica to the flask and stir for 10min, then add 1g polydimethylsiloxane and 1.5g KH560 to the flask and stir for 10min, finally add 25g 593 epoxy resin amine curing agent to the reaction system and stir for 10min to obtain a uniformly mixed epoxy resin, then pour the prepared epoxy resin into a molding mold, put it into a constant temperature and humidity chamber at 25℃ and 50%RH for curing for 24h to obtain a sound backing material. The density of the epoxy resin cured product is 1.16g / cm 3, the sound velocity is 2415m / s, the acoustic impedance is 2.8MRayl, the acoustic attenuation at a frequency of 2.25MHz is 81.30dB / cm, and the thermal conductivity is 0.223W / m*k.

[0140] Embodiment 11

[0141] Add 100g E51 epoxy resin to a 250ml flask, add 20g acrylic resin to the flask and stir for 10min, add 0.6g fumed silica to the flask and stir for 10min, then add 1g polydimethylsiloxane and 1.5g KH560 to the flask and stir for 10min, finally add 25g 593 epoxy resin amine curing agent to the reaction system and stir for 10min to obtain a uniformly mixed epoxy resin, then pour the prepared epoxy resin into a molding mold, put it into a constant temperature and humidity chamber at 25℃ and 50%RH for curing for 24h to obtain a sound backing material. The density of the epoxy resin cured product is 1.16g / cm 3 , the sound velocity is 2465m / s, the acoustic impedance is 2.86MRayl, the acoustic attenuation at a frequency of 2.25MHz is 82.04dB / cm, and the thermal conductivity is 0.22W / m*k.

[0142] It can be seen from Examples 1 and 8 to 11 that as the amount of acrylic acid added increases, the sound attenuation of the material gradually increases, and when the amount of acrylic acid reaches 10g, 15g, and 20g, the sound attenuation approaches stability.

[0143] Effect Example

[0144] The products in the above embodiments and comparative examples were tested for acoustic impedance, acoustic attenuation at a frequency of 2.25 MHz, acoustic velocity, and density.

[0145] 1. Density

[0146] The formula for density can be expressed as:

[0147] ρ=m / v

[0148] Wherein, m is the mass of the test sample, and v is the volume of the test sample;

[0149] 2. Sound velocity, sound attenuation and sound impedance

[0150] The water immersion insertion method is used to measure the sound velocity and sound attenuation. In order to obtain more accurate results, each test sample is usually measured with two different thicknesses. The sound velocity c, acoustic impedance Z and sound attenuation coefficient α can be obtained by calculation. The sound velocity and sound attenuation coefficient can be expressed as:

[0151]

[0152]

[0153] Among them, l1 and l2 are the thickness of the test sample, △l is the thickness difference of the inserted sample, △t is the sound propagation time difference caused by inserting samples of different thicknesses, and c w is the speed of sound in water, α w is the acoustic attenuation coefficient in water, A1 and A2 are the pulse signal amplitudes received when testing samples with thicknesses of l1 and l2 respectively.

[0154] The formula for acoustic impedance can be expressed as:

[0155] Z=ρ*c

[0156] Where ρ is the density of the test sample and c is the speed of sound in the test sample.

[0157] 3. Viscosity

[0158] The viscosity test method is in accordance with GB / T22314-2008- "Plastic Epoxy Resin Viscosity Determination Method", and the viscosity can be obtained by calculation; the viscosity of the liquid sample is measured by a rotational viscometer based on the shear rate used and the shear stress obtained. The viscosity η is defined by the following formula: η=τ / γ,

[0159] Where:

[0160] η——Viscosity, in Pascal seconds (Pa*s)

[0161] τ——shear force, in Pascal (Pa)

[0162] γ——shear speed, in s per second -1 ).

[0163] 4. Thermal conductivity

[0164] The thermal conductivity coefficient adopts the international standard ISO 22007-2 "Plastics. Determination of thermal conductivity and thermal diffusivity". By testing the relationship between the temperature rise of the sample and time, the thermal conductivity coefficient of the sample is obtained by using a mathematical model to fit.

[0165] The principle of this method is to place a temperature probe with a self-heating function in the sample, and apply a constant heating power to the probe during the test to increase its temperature. The relationship between the thermal resistivity of nickel - temperature and resistance is linear, that is, the heat loss can be known by understanding the change in resistance, thereby reflecting the thermal conductivity of the sample. Then measure the relationship between the temperature rise over time on the probe itself and the spherical surface at a certain distance from the probe, and obtain the thermal conductivity and thermal diffusivity of the sample at the same time through mathematical model fitting.

[0166] The performance effects of the products obtained in the above examples and comparative examples are shown in Table 1 below.

[0167] Table 1

[0168]

[0169]

[0170] The present invention includes but is not limited to the above embodiments. Any equivalent or partial replacement made under the concept of the present invention shall be deemed to be within the protection scope of the present invention.

Claims

1. A method for preparing a backing material, characterized in that: The method comprises the following steps: mixing and reacting a raw material composition of a backing material to obtain a backing material; The raw material composition of the backing material includes epoxy resin, acrylic resin and amine curing agent; The average molecular weight of the epoxy resin is 350-400, and the epoxy equivalent is 175-200 g / eq; the average molecular weight of the acrylic resin is 70-200, and the viscosity is 20000-40000 CP; The mass ratio of the epoxy resin to the acrylic resin is (4-25):1; The mass ratio of the epoxy resin to the amine curing agent is (3-5):1; The mixing method is a mechanical stirring method; Acrylic resin is introduced into the backing material, and the acrylic resin reacts with the amine curing agent, the system is phase-separated, and a multiphase interface is formed. The number of interfaces of the backing material is increased, which is beneficial to improving the refraction and reflection of sound waves. Sound energy is continuously refracted and reflected in the multiphase interface, and the energy of the sound waves is reduced and converted into heat energy, which is finally dissipated, thereby improving the sound attenuation of the backing system.

2. The method for preparing the backing material according to claim 1, characterized in that: The raw material composition of the backing material satisfies one or more of the following conditions (1) to (4): (1) The epoxy resin is a glycidyl ether epoxy resin; (2) The acrylic resin is obtained by polymerizing one or more monomers selected from the group consisting of methyl acrylate, methyl methacrylate, ethyl methacrylate and propyl methacrylate; (3) The raw material composition of the backing material further includes one or more of tungsten powder, lead powder and alumina powder; (4) The raw material composition of the backing material further includes one or more of a thixotropic agent, a defoaming agent and a coupling agent.

3. The method for preparing the backing material according to claim 1, characterized in that: The raw material composition of the backing material satisfies one or more of the following conditions (5) to (8): (5) The epoxy resin is one or more of E51 bisphenol A epoxy resin, aluminum oxide modified epoxy resin, semi-silicone modified bisphenol A epoxy resin, hyperbranched epoxy resin, bisphenol A epoxy hybrid resin, silicon-titanium hybrid epoxy resin and acrylic acid modified alkyd-epoxy ester hybrid resin; (6) The mass ratio of the epoxy resin to the acrylic resin is (5-25):1; (7) The amine curing agent is a 593 type epoxy resin amine curing agent; (8) The mass ratio of the epoxy resin to the amine curing agent is 4:

1.

4. The method for preparing the backing material according to claim 3, characterized in that: The epoxy resin is E51 bisphenol A epoxy resin; And / or, the mass ratio of the epoxy resin to the acrylic resin is 5:1, 6.67:1, 10:1, 12.5:1 or 25:

1.

5. The method for preparing the backing material according to claim 2, characterized in that: The raw material composition of the backing material satisfies one or more of the following conditions (9) to (17): (9) The mass ratio of the epoxy resin to the tungsten powder is (4-6):1; (10) The mass ratio of the epoxy resin to the lead powder is (8-12):1; (11) The mass ratio of the epoxy resin to the alumina is (18-22):1; (12) The thixotropic agent is fumed silica; (13) The mass ratio of the epoxy resin to the thixotropic agent is (150-180):1; (14) The defoaming agent is polydimethylsiloxane; (15) The mass ratio of the epoxy resin to the defoaming agent is (90-110):1; (16) The coupling agent is one or more of the silane coupling agents KH550, KH560 and KH570; (17) The mass ratio of the epoxy resin to the coupling agent is (60~70):

1.

6. The method for preparing the backing material according to claim 5, characterized in that: The mass ratio of the epoxy resin to the tungsten powder is 5:1; And / or, the mass ratio of the epoxy resin to the lead powder is 10:1; And / or, the mass ratio of the epoxy resin to the alumina is 20:1; And / or, the mass ratio of the epoxy resin to the thixotropic agent is 166.7:1; And / or, the mass ratio of the epoxy resin to the defoaming agent is 100:1; And / or, the mass ratio of the epoxy resin to the coupling agent is 66.7:

1.

7. The method for preparing the backing material according to claim 1, characterized in that: The raw material composition of the backing material comprises epoxy resin, acrylic resin, amine curing agent, tungsten powder, lead powder, aluminum oxide powder, thixotropic agent, defoaming agent and coupling agent.

8. The method for preparing the backing material according to claim 7, wherein: Calculated by mass fraction, the raw material composition of the backing material includes 100 g of epoxy resin, 4-25 g of acrylic resin, 25 g of amine curing agent, 20 g of tungsten powder, 10 g of lead powder, 5 g of aluminum oxide, 0.6 g of thixotropic agent, 1 g of defoaming agent and 1.5 g of coupling agent.

9. The method for preparing a backing material according to claim 1, wherein: The reaction temperature is 15-25°C; And / or, the relative humidity of the reaction is 40-60% RH; And / or, the reaction time is 12 to 48 hours.

10. A backing material, characterized in that: The backing material is prepared by the method for preparing the backing material as described in any one of claims 1 to 9.

11. The backing material according to claim 10, characterized in that The backing material satisfies one or more of the following conditions (18) to (22): (18) The density of the backing material is 1.0~6.0 g / cm 3 ; (19) The sound velocity of the backing material is 1600~2500 m / s; (20) The acoustic impedance of the backing material is 2.5-10 Mray; (21) The backing material has an acoustic attenuation of 70 to 90 dB / cm at a frequency of 2.25 MHz; (22) The thermal conductivity of the backing material is 0.2~1.6 W / m·K.

12. The backing material according to claim 11, wherein The density of the backing material is 1.16-5.63 g / cm 3 ; And / or, the sound velocity of the backing material is 1650-2465 m / s; And / or, the acoustic impedance of the backing material is 2.68-9.43 Mray; and / or, the backing material has an acoustic attenuation of 73.51-89.05 dB / cm at a frequency of 2.25 MHz; And / or, the thermal conductivity of the backing material is 0.22-1.54 W / m·K.

13. The backing material according to claim 11, wherein The density of the backing material is 1.16 g / cm 3 , 1.78 g / cm 3 , 1.8 g / cm 3 , 1.96 g / cm 3 4.46 g / cm 3 , 5.6 g / cm 3 or 5.63 g / cm 3 ; and / or, the sound velocity of the backing material is 1650 m / s, 1675 m / s, 1690 m / s, 2189 m / s, 2200 m / s, 2310 m / s, 2315 m / s, 2323 m / s, 2415 m / s or 2465 m / s; and / or, the backing material has an acoustic impedance of 2.68 Mray, 2.69 Mray, 2.7 Mray, 2.8 Mray, 2.86 Mray, 3.96 Mray, 4.13 Mray, 4.29 Mray, 7.54 Mray, 9.24 Mray or 9.43 Mray; and / or the backing material has an acoustic attenuation of 73.51 dB / cm, 80 dB / cm, 80.53 dB / cm, 81.30 dB / cm, 81.84 dB / cm, 82.03 dB / cm, 82.04 dB / cm, 83.07 dB / cm, 88.54 dB / cm, 88.74 dB / cm or 89.05 dB / cm at a frequency of 2.25 MHz; And / or, the thermal conductivity of the backing material is 0.22 W / m·K, 0.221 W / m·K, 0.223 W / m·K, 0.27 W / m·K, 0.33 W / m·K, 0.42 W / m·K, 1.532 W / m·K, 1.538 W / m·K or 1.54 W / m·K.

14. An ultrasonic probe, characterized in that: It comprises the backing material according to any one of claims 10-13.

15. An ultrasonic diagnostic device, characterized in that: It comprises the ultrasound probe as claimed in claim 14.

Citation Information

Patent Citations

  • Preparation method of high-attenuation backing material

    CN104552718A

  • Backing component in ultrasound probe

    CN109907775A

  • Backing material for ultrasonic detection probe and manufacturing method thereof

    CN1605863A

  • Backing material and preparation method thereof, and ultrasonic wave probe

    CN110819073A

  • Acoustic matching layer material, acoustic matching layer, ultrasonic transducer, ultrasonic probe, ultrasonic imaging device and preparation method

    CN115141466A